Essential fracture and orthopaedic equipment lists in low resource settings: consensus derived by survey of experts in Africa. Issue 9 (17th September 2018) - Chan, Yuen; Banza, Leonard; Martin Jr, Claude; Harrison, William J
Abstract : Introduction: Low/middle-income countries (LMICs) have a growing need for trauma and orthopaedic (T&O) surgical interventions but lack surgical resources. Part of this is due to the high amount of road traffic accidents in LMICs. We aimed to develop recommendations for an essential list of equipment for three different levels of care providers. Methods: The Delphi method was used to achieve consensus on essential and desirable T&O equipment for LMICs. Twenty experts with T&O experience from LMICs underwent two rounds of questionnaires. Feedback was given after each round of questionnaires. The first round of questionnaire consisted of 45 items graded on a Likert scale with the second round consisting of 50 items. We used an electronic questionnaire to collect our data for three different levels of care: non-operative-based provider, specialist provider with operative fracture care and tertiary provider with operative fracture care and orthopaedics. Results: After two rounds of questionnaires, recommendations for each level of care in LMICs included 4 essential equipment items for non-operative-based providers; 27 essential equipment items for specialist providers with operative fracture care and 46 essential equipment items for tertiary providers with operative fracture care and orthopaedic care. Conclusion: These recommendations can facilitate in planning of appropriate equipment required in an institution which in turn has the potential to improve the capacity and quality of T&O care in LMICs. The essential equipment lists provided here can help direct where funding for equipment should be targeted. Our recommendations can help with planning and organising national T&O care in LMICs to achieve appropriate capacity at all relevant levels of care.